Peran Notaris Dalam Pembuatan Akta Waris Pasca Pergeseran Norma Waris Adat Bali - Jaya, Komang Tri Setia; Jamin, Mohammad; Mulyanto, Mulyanto (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023), 2023)
This study aims to determine the inheritance system in Wia-Wia Village after the Majelis Utama Desa Pakraman Bali Decision Number 01/Kep/Psm-3/MDP Bali/X/2010, to determine the legal validity of the decision to subsequently be used as a basis for Notaries in making inheritance deeds for Balinese indigenous people in Wia-Wia Village, and to find out the role of Notaries in making inheritance deeds based on Balinese customary law in Wia-Wia Village. This research is of empirical juridical type. The approach used is the approach of legislation and sociology of law. The data collection technique is by direct observation and semi-structured interviews. All data that has been collected is then analyzed with qualitative techniques. Then the results of this study show: (1) the people of Wia-Wia Village still adhere to a patrilineal belief system, namely heirs fall to purusa descendants (male) and predana descendants (female) do not get inheritance; (2) Majelis Utama Desa Pakraman Bali Decision Number 01/Kep/Psm-3/MDP Bali/X/2010 does not necessarily bind the Balinese indigenous people in Wia-Wia Village. Therefore, the decision cannot be used as a legal basis by the Notary in making an inheritance deed for the Balinese indigenous people in Wia-Wia Village; and (3) the role of Notaries in making inheritance deeds for Balinese indigenous people in Wia-Wia Village is limited to the act of pouring the will of the Balinese Indigenous people in Wia-Wia Village who face them by taking into account the values of Balinese customary law that they still adhere to today.